Present and future are getting confused: are we equipped to face the technological revolution? - Giorgio Perilongo; Rino Agostiniani; Giovanni Corsello; Gianluigi Marseglia; Maurizio Muraca; Anna Maria Staiano; Gianvincenzo Zuccotti; Eugenio Baraldi; For the Commission of Technology Innovation in Pediatrics, Italian Society of Pediatrics (BMC, 2023)
Abstract Background This is a commentary reporting the outcome of a workshop promoted by the Department of Woman's and Child's Health of the University of Padua (Italy) focused on the emerging issue of what seems to be the increasing agemone role of technology. Main body Over the centuries, technology has always been at the service of science, with theoretical insights anticipating experimental proofs. Over the last decades, however, the situation has radically changed, due to several factors. Technology seems to be playing an agemone role. The present and notably the future generation of scientists have major challenges to face. They have to deal with the forces generated by the infosphera; to dominate the technology and to maintain the capacity of generating inquisitive, creative, ethical and spiritual thoughts capable of addressing new scientific hypotheses and projects directed to the individual and collective good. However, in this scenario, what seems more relevant is to focus all our efforts in preparing ourselves, first, and then the new generations to face these challenges. From this point of view, the academic institutions and the scientific societies, have a major responsibility to deal with. Conclusions The academic ecosystem traditionally used to educate the new generation of professionals as well as, and most importantly, the cultural, the professional pathways presently used to form them need to be extensively revised. The time is running short and the stakes are high. The debate is open.